The Role of state forest enterprises on benefit sharing through payments for environmental services in Vietnam: a paradigm shift. [Abstract only]. - Milan, Florence M.; Huong, T.T.T.; Hoanh, Chu Thai; Phuong, N. D. (2013)
One challenge to overcome in implementing payment for environmental services (PES) in Vietnam is the high transaction cost associated with many contracts with small scale ecosystem service providers. In order to promote pro-poor PES, it is necessary to identify institutional options that reduce transaction costs and organizational problems. State Forest Enterprises (SFEs) play an important role in the forestry sector and the livelihoods of many rural poor in the country. The government of Vietnam has issued Decree 200 in December 2004 to develop provincial SFE reform plans. SFEs were given much greater autonomy and the government expected an increase in land managed directly by households (and possibly communities) under district level administration rather than the provincial level aimed at improving economic and social opportunities in the locality of SFEs. The main challenges to implement the reform were availability of government funds and availability of loans for SFEs (EASRD, 2005). The Development Assistant Fund recently increased interest rates and introduced more stringent lending criteria making access to financing difficult for SFEs. By linking available revenue sharing funds from hydropower dam projects to SFEs, these SFEs may be able to expand and implement PES programs cost-effectively. Therefore, we are looking into the policy and legal framework of SFEs in Vietnam as well as its operational procedures to look into potential application of benefit sharing through PES. The study undertakes three stages: First, a review on policy and legal frameworks of SFEs enables us to determine if the system is conducive to managing benefit sharing of hydropower dam projects. Second, on-going SFE models in Vietnam are reviewed and evaluated in terms of benefit sharing applicability within the hydropower dam context. Finally, empirical data from Tu Ly SFE is analysed to draw on a mechanism of benefit sharing through PES. Households who participated in the loan program of the Tu Ly SFE are interviewed to elicit information on household characteristics, cost and benefits of joining the Tu Ly SFE loan program, and their loan use. In addition, individuals paid by the Tu Ly SFE to plant and manage the forest are interviewed. Finally, the study presents a framework of benefit sharing of hydropower dam projects through payments for environmental services managed by SFEs developed from the above analysis with an assessment of advantages and challenges in its implementation.